Factors Influencing Health Workers’ Compliance with Nosocomial Infection Prevention Procedures in Hand Washing in the Maternity Ward of RSAU Dr. Esnawan Antariksa - Dian Mahanani (Ammar Dharma Foundation, 2024)
Background: Hand washing is the process of thoroughly cleaning the hands, starting from the fingertips, elbows, and arms, as needed. It involves knowledge, behavior, attitudes, facilities, and supervision.Objective: This study aims to determine the hand washing practices of healthcare workers at RSAU Dr. Esnawan Antariksa in 2023.Research Method: This research design uses a simple correlational method with a cross-sectional study approach to determine the relationship between variables in the correlational results concerning the hand washing practices of healthcare workers.Results: Based on the research results, 94.3% of respondents demonstrated good hand washing practices, 91.4% exhibited good behavior, 97.1% showed good attitudes, 94.3% displayed good knowledge, 97.1% reported the availability of facilities, and 88.6% reported the presence of supervision.Conclusion: Statistical tests showed no significant effect on behavior (P=0.656), attitudes (P=0.803), knowledge (P=0.720), facilities (P=0.803), or supervision (P=0.601) at an α level of 0.05.